2021
DOI: 10.1002/pros.24222
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte‐to‐monocyte ratio is a predictor of clinically significant prostate cancer at prostate biopsy

Abstract: Background Inflammation plays critical roles at different stages of carcinogenesis and cancer progression. Several previous studies showed conflicting results for the predictive role of systemic inflammation markers in the detection of clinically significant prostate cancers (CSPCs). We aimed to determine the predictive roles of lymphocyte‐to‐monocyte (LMR) and eosinophil‐to‐lymphocyte ratios (ELR) in the detection of CSPC at standard 12‐core transrectal ultrasound‐guided prostate biopsy (12‐core‐TRUS‐Bx) usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
4
2
Order By: Relevance
“…We identified NLR and PLR as potential predictors of LNM in PCa based on ROC analysis and multivariate regression analysis, for which we observed that NLR (cutoff: 1.72) and PLR (cutoff: 83.305) were more likely to predict LNM when they were lower than the optimal cutoff value, though there was not super high sensitivity for hematological indices. Increases in PLR and NLR, as well as decreases in LMR, have been related to poorer overall survival outcomes in many cancers including PCa, 36,37 contradicting our results by a certain extent. We speculate that these differences may be associated with the stimulation of lymphocyte release from lymph nodes into the peripheral blood following tumor cell metastasis to these nodes.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…We identified NLR and PLR as potential predictors of LNM in PCa based on ROC analysis and multivariate regression analysis, for which we observed that NLR (cutoff: 1.72) and PLR (cutoff: 83.305) were more likely to predict LNM when they were lower than the optimal cutoff value, though there was not super high sensitivity for hematological indices. Increases in PLR and NLR, as well as decreases in LMR, have been related to poorer overall survival outcomes in many cancers including PCa, 36,37 contradicting our results by a certain extent. We speculate that these differences may be associated with the stimulation of lymphocyte release from lymph nodes into the peripheral blood following tumor cell metastasis to these nodes.…”
Section: Discussioncontrasting
confidence: 96%
“…A growing number of studies have found 68 Ga-PET/CT to offer significant value when diagnosing LNM. [25][26][27][28] As one of the primary Increases in PLR and NLR, as well as decreases in LMR, have been related to poorer overall survival outcomes in many cancers including PCa, 36,37 contradicting our results by a certain extent. We speculate that these differences may be associated with the stimulation of lymphocyte release from lymph nodes into the peripheral blood following tumor cell metastasis to these nodes.…”
Section: Discussioncontrasting
confidence: 81%
“…20,21 Many research groups have investigated the predictive and prognostic roles of peripheral blood inflammatory parameters in prostate cancer. [22][23][24] Cho et al 23 reported that the lymphocyte-to-monocyte ratio is a predictor of clinically significant prostate cancer on prostate biopsy. Bauckneht et al 24 also found that a higher neutrophil-to-lymphocyte ratio and systemic inflammation index predicted worse OS in patients with prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…(3) In addition, the high cost of such additional approaches is the greatest obstacle to their widespread use in clinical practice. (4) It is known that low IPSS score and positive rectal examination (stiffness) increase the probability of being diagnosed with cancer in patients with PSA levels in the gray zone. (5) But there is still a need for markers that can be measured with a low cost in a non-invasive manner, especially to identify clinically significant PCa (csPCa).…”
Section: Introductionmentioning
confidence: 99%
“…*Statistically significant at p<0.05.DÜNDAR & ERKAN : MLR Predicts Prostate Cancer ne system, is associated with a poor prognosis in various cancers. (16) There are few studies in the literature that draw attention to the role of MLR in the prediction of PCa (4,11,12). In this retrospective study, we evaluated whether MLR had a potential role as a biomarker of PCa activity based on clinicopathological data.…”
mentioning
confidence: 99%